2012
DOI: 10.4103/2230-8210.95682
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GnRH analogue testing in diagnosis and management of children with pubertal disorders

Abstract: Context:Gonadotrophin releasing hormone (GnRH) stimulation test is pivotal in the assessment of children with pubertal disorders. However, lack of availability and high cost often result in the test falling into disfavor. We routinely use the GnRH analogue stimulation test as an alternative at our center.Aim:To present the data on children with endocrine disorders who underwent GnRH agonist stimulation test in pediatric endocrine clinic of a tertiary care referral hospital.Setting and Design:Pediatric endocrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Challenges arise in distinguishing between true pathological causes of CPP, isolated premature thelarche in girls (nonprogressive variants), and early phases of normal puberty [ 3 , 6 ].…”
Section: Gonadotropin-dependent Precocious Pubertymentioning
confidence: 99%
See 3 more Smart Citations
“…Challenges arise in distinguishing between true pathological causes of CPP, isolated premature thelarche in girls (nonprogressive variants), and early phases of normal puberty [ 3 , 6 ].…”
Section: Gonadotropin-dependent Precocious Pubertymentioning
confidence: 99%
“…Prepubertal basal level of serum estradiol can reach down to 1 pg/mL and that of serum testosterone to <10 ng/dL, measurable with a highly sensitive method (i.e., tandem mass spectrometry) [ 14 ]. Basal serum testosterone >25 ng/dL to >75 ng/dL in boys and estrogen level >10 pg/mL, >12 pg/mL, or >20 pg/mL in girls have been used as cutoff values for puberty [ 1 , 3 , 22 , 23 ]. With the GnRH test, peak values for both hormones are usually seen after 16 to 24 hours post-stimulation [ 1 , [ 3 ]].…”
Section: Gonadotropin-dependent Precocious Pubertymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, studies have reported different specificity, sensitivity and cutoff values for GnRH (3,4). Many factors, including the specificities of follicle stimulating hormone (FSH) and luteinizing hormone (LH) assays, influence GnRH test results (5). Estradiol measurements are less reliable indicators of the stage of puberty (2).…”
Section: Introductionmentioning
confidence: 99%